A Research on Metaphors for the “Future” Created by High School Students - Mustafa Doğan; Fatih Yılmaz; Celalettin Çelebi (Sakarya University Journal of Education)
Abstract. Adolescence is a period of significant changes, during which the individual makes many plans for the future. Some researches reveal that individuals in adolescence may also be prone to making wrong decisions, if they are deprived of the necessary guidance during this period. It can be a problematic period for the individual, parents, friends, relatives etc. Thus, the researchers think that the results of this study will guide various future studies. This period coincides with high school period taking The World Health Organization's definition of adolescence, grade levels and ages of students in our country into consideration. Moreover, metaphors which have an important place in daily life and are widely used, can be a research topic in various disciplines. The purpose of this research is to reveal the metaphors produced by high school students about future. The research data, have been collected from 144 high school students living in Turkey and analyzed by means of content analysis. At the end of the research, 96 metaphors have been created in fifteen categories on four themes. Finally, the findings have been discussed taking the results of various studies in the literature into consideration, and some suggestions have also been made.